A Cheerleader, a Snapchat, and a Profanity go to Supreme Court but the Punchline in Mahanoy Isn't Funny. Issue 2 (8th July 2022) - Terry, Christopher; Schmitz, Stephen; Silberberg, Eliezer Joseph
Abstract: In Reno v. ACLU and Packingham v. North Carolina, the U.S. Supreme Court ruled that government-enacted restrictions on online speech must pass strict scrutiny review. Even so, efforts to compel and restrict speech appearing in private venues like social media continue to expand in scope and number at both the state and federal level. We first explore Mahanoy Area School District v. B.L. in the context of student speech cases before discussing how the decision destroys the traditional boundary of the schoolhouse gate for the regulation of student speech. It does so despite the fact that the cheerleader's profane messages would have been protected expression in any nonschool situation. We then argue that Mahanoy, despite being an individual win for the cheerleader, illustrates how the Court continues to wrestle with traditional applications of the First Amendment to internet speech. We argue that the decision has the regulation of internet speech following a path similar to the regulation of broadcast speech.